Correlation between Microalbuminuria and Ultrasonographically Measured Carotid Intima Media Thickness in Type 2 Diabetic Subjects - Taher, Md. Abu; Malek, Musarrat Abdul; Rahmen, Nayema; Abedin, Naffisa; Shegufta, Farzana; Sharif, Md. Mofazzal; Rahman, Md. Towhidur (BIRDEM Medical Journal, 2013)
Background: Microalbuminuria is associated with increased cardiovascular mortality in type 2 Diabetes mellitus. Carotid intima media thickness reflects index of cardiovascular disease. There is increased prevalence of microalbuminuria found in type 2 diabetes. So there is a positive correlation between microalbuminuria and carotid intima media thickness in type 2 diabetic subjects. Objective: This study was performed to find out correlation between microalbuminuria and ultrasonographically measured carotid intima media thickness in type 2 diabetic subjects. Materials and methods: The cross-sectional study was carried out in the Department of Radiology & Imaging, BIRDEM from 1st june 2011 to 31st may 2012. A total number of 90 type 2 diabetic patients with microalbuminuria were included. All the subjects underwent B mode sonographic imaging of the extracranial carotid arteries. The intima media thickness of both left and right side was recorded. Urinary albumin and creatinine were measured in random urine samples. The urinary albumin concentration was determined by turbidimetric immuneassay (TIA) with the use of superior microalbumin kit and creatinine was measured by Jaffes reaction. Albumin-to-Creatinine Ratio (ACR) was calculated. Results: The total number of patient was 90,male were 68 and female were 22 (Male female ratio was 3.09:1). Mean age was 55.6 years with standard deviation(SD) ± 6.06 years (Range 45-65 years).The mean ACR was 78.9 mg/g with standard deviation(SD) ± 21.8 mg/g (Range 33 to 111 mg/g). The mean intima-media thickness of carotid arteries was 1.04 mm with standard deviation (SD) ±0.19 mm. Significant positive correlation was found between albumin-to-creatinine ratio (ACR) and intima-media thickness of carotid arteries (CIMT) in type 2 diabetic subjects. The value of Pearsons correlation was r= 0.583, which is significant (p<0.01). Therefore, there was a linear positive correlation between albumin-tocreatinine ratio (ACR) and intima-media thickness of carotid arteries (CIMT) in type 2 diabetic subjects. Conclusion:From this cross-sectional study it can be concluded that there is a significant positive correlation between microalbuminuria and ultrasonographically measured carotid intima media thickness in type 2 diabetic subjects. Birdem Med J 2013; 3(2): 85-89 DOI: http://dx.doi.org/10.3329/birdem.v3i2.17211